A Children's Music Therapy to Enhance the Self-Esteem of Children with Attention Deficit Hyperactivity Disorder (ADHD) in Elementary School - Abdul Sholeh; Asep Supena (IAIN Syekh Nurjati Cirebon, 2021)
AbstractElementary school students with Attention Deficit Hyperactivity Disorder (ADHD) possessed low self-eesteem that impacted on their academic failure. This study aims to describe the use of a children’s music therapy to enhance the self-esteem of ADHD students. Using a qualitative case study to garner the data from ADHD students, this study included pre-field stages, activities during the field, and post empirical stages. Data were analyzed using observations and interviews. The results of the research show that the children’s music therapy can be used as an alternative in developing the self-esteem of ADHD children in an elementary school. It can be seen from their development of several aspects including ability (competence), meaning (significance), goodness (virtue), and strength (power). Therefore, elementary school teachers are advised to use the music therapy to enhance the self-esteem of ADHD children. As a medium of healing and to overcome anxiety, such therapy could allow students to gain self-acceptance, get acceptance by others, be able to complete tasks, be able to make decisions, be able to control themselves, and have better self-awareness.Keywords: a children's music therapy, self-esteem, attention deficit hyperactivity disorder.AbstrakSiswa sekolah dasar dengan Attention Deficit Hyperactivity Disorder (ADHD) memiliki harga diri yang rendah yang berdampak pada kegagalan akademik mereka. Penelitian ini bertujuan untuk mendeskripsikan penggunaan terapi musik anak untuk meningkatkan harga diri siswa ADHD. Menggunakan studi kasus kualitatif untuk mengumpulkan data dari siswa ADHD, penelitian ini meliputi tahap pra-lapangan, kegiatan selama lapangan, dan tahap pasca empiris. Teknik analisis data menggunakan observasi dan wawancara. Hasil penelitian menunjukkan bahwa terapi musik anak dapat digunakan sebagai salah satu alternatif dalam mengembangkan harga diri anak ADHD di sekolah dasar. Hal ini dapat dilihat dari perkembangannya dari beberapa aspek antara lain kemampuan (competence), makna (significance), kebaikan (virtue), dan kekuatan (power). Oleh karena itu, guru sekolah dasar disarankan untuk menggunakan terapi musik untuk meningkatkan harga diri anak ADHD. Sebagai media penyembuhan dan mengatasi kecemasan, terapi tersebut dapat memungkinkan siswa untuk memperoleh penerimaan diri, mendapatkan penerimaan oleh orang lain, mampu menyelesaikan tugas, mampu mengambil keputusan, mampu mengendalikan diri, dan memiliki kesadaran diri yang lebih baik.Kata kunci: terapi musik anak, harga diri, attention deficit hyperactivity disorder.